Late Holocene earthquakes on the Toe Jam Hill fault, Seattle fault zone, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Kelsey, H. M.; Wells, R. E.; Sherrod, B. L.; Pezzopane, S. K.; Bradley, L. A.; Koehler, R. D.; Bucknam, R. C. (Geological Society of America Bulletin, 2003)
Five trenches across a Holocene fault scarp yield the first radiocarbon-measured earthquake recurrence intervals for a crustal fault in western Washington. The scarp, the first to be revealed by laser imagery, marks the Toe Jam Hill fault, a north-dipping backthrust to the Seattle fault. Folded and faulted strata, liquefaction features, and forest soil A horizons buried by hanging-wall-collapse colluvium record three, or possibly four, earthquakes between 2500 and 1000 yr ago. The most recent earthquake is probably the 1050-1020 cal. (calibrated) yr B.P. (A.D. 900930) earthquake that raised marine terraces and triggered a tsunami in Puget Sound. Vertical deformation estimated from strati-graphic and surface offsets at trench sites suggests late Holocene earthquake magnitudes near M7, corresponding to surface ruptures >36 km long. Deformation features recording poorly understood latest Pleistocene earthquakes suggest that they were smaller than late Holocene earthquakes. Postglacial earthquake recurrence intervals based on 97 radiocarbon ages, most on detrital charcoal, range from similar to12,000 yr to as little as a century or less; corresponding fault-slip rates are 0.2 mm/ yr for the past 16,000 yr and 2 mm/yr for the past 2500 yr. Because the Toe Jam Hill fault is a backthrust to the Seattle fault, it may not have ruptured during every earthquake on the Seattle fault. But the earthquake history of the Toe Jam Hill fault is at least a partial proxy for the history of the rest of the Seattle fault zone.
740qwTimes Cited:41Cited References Count:53